Tax Buoyancy for Sustainable Development: A Development Law Perspective in Indonesia - Henry D.P. Sinaga; Anis W. Hermawan (Scientia Integritas Utama, 2022)
Tax ratio predictions cannot be separated from the weak and strong of tax buoyancy. However, calculating the effect of tax buoyancy on the tax ratio, which is still dominated by the philosophy of positivism, must be shifted to the concept of development law considering that low tax buoyancy values indicate low tax elasticity and ineffective discretionary changes. Based on the conceptual framework of development law, it is concluded that tax buoyancy which tends to change must be improved by increasing tax income and by changing discretionary changes in order to achieve the ideal tax ratio in achieving sustainable development, namely 15%. Efforts can be made by focusing on factors that influence tax buoyancy, namely extensification, intensification and increasing the effectiveness of law enforcement in sectors that have an impact on increasing the tax ratio as seen from tax buoyancy, as well as administration, regulations, and tax authorities’ capacity improvements.